Sistem Manajemen Informasi Notulensi Rapat Pada Biro Pemerintahan Dan Otonomi Daerah Di Kantor Gubernur Sumatera Utara - Aidil Akbar Simatupang; Harun Al Rasyid; Mhd Ikhsan Rifki (Journal Of Informatics And Busisnes, 2024)
Meeting management is a series of activities aimed at planning, organizing, implementing and evaluating a meeting or meeting to achieve certain goals. The Bureau of Government and Regional Autonomy at the Office of the Governor of North Sumatra functions as a technical institution that handles government affairs and regional autonomy under the coordination of the governor. It is not uncommon for this bureau to hold meetings every day. When holding a meeting, meeting management such as attendance lists and meeting minutes are still done manually using paper and recorded by hand and then stored in a storage room. Manual processes like this tend to be time consuming and can increase the risk of errors. Seeing this problem, the need for the process of checking information on availability and confirming the borrowing of a room to be used for meetings takes a relatively longer time so it becomes an obstacle. The aim is to design and implement an effective information management system to increase the efficiency of meeting minutes in government bureaus and regional autonomy. This system was built by modeling several UML diagrams such as use case diagrams, activity diagrams, and class diagrams. It is hoped that the Bureau of Government and Regional Autonomy at the Office of the Governor of North Sumatra can improve the quality of education which can be realized through the appropriate and efficient use of information technology.